Probing the polarized emission from SMC X-1: The brightest X-ray pulsar observed by IXPE - Forsblom, Sofia V.; Tsygankov, Sergey S.; Poutanen, Juri; Doroshenko, Victor; Mushtukov, Alexander A.; Ng, Mason; Ravi, Swati; Marshall, Herman L.; Di Marco, Alessandro; La Monaca, Fabio; Malacaria, Christian; Mastroserio, Guglielmo; et al. (EDP Sciences, 2025)
Recent observations of X-ray pulsars (XRPs) performed by the Imaging X-ray Polarimetry Explorer (IXPE) have made it possible to investigate the intricate details of these objects in a new way, thanks to the added value of X-ray polarimetry. Here we present the results of the IXPE observations of SMC X-1, a member of the small group of XRPs displaying super-orbital variability. SMC X-1 was observed by IXPE three separate times during the high state of its super-orbital period. The observed luminosity in the 2–8 keV energy band of L ∼ 2 × 1038 erg s−1 makes SMC X-1 the brightest XRP ever observed by IXPE. We detect significant polarization in all three observations, with values of the phase-averaged polarization degree (PD) and polarization angle (PA) of 3.2 ± 0.8% and 97° ±8° for Observation 1, 3.0 ± 0.9% and 90° ±8° for Observation 2, and 5.5 ± 1.1% and 80° ±6° for Observation 3, for the spectro-polarimetric analysis. The observed PD shows an increase over time with decreasing luminosity, while the PA decreases in decrements of ∼10°. The phase-resolved spectro-polarimetric analysis reveals significant detection of polarization in three out of seven phase bins, with the PD ranging between ∼2% and ∼10%, and a corresponding range in the PA from ∼70° to ∼100°. The pulse-phase resolved PD displays an apparent anti-correlation with the flux. Using the rotating vector model, we obtain constraints on the pulsar’s geometrical properties for the individual observations. The position angle of the pulsar displays an evolution over time supporting the idea that we observe changes related to different super-orbital phases. Scattering in the wind of the precessing accretion disk may be responsible for the behavior of the polarimetric properties observed during the high-state of SMC X-1’s super-orbital period.